Mortality and morbidity patterns in measles cases admitted to the hospitals in Yogyakarta - Djauhar Ismail Djauhar Ismail (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1997)
The case fatality rate of measles cases admitted to the hospitals in Indonesia in the period of 1973 -1989 varied from as high as 26.1% in Medan to 2.4% in Bali, with an average of 10.9% in all hospitals. In Indonesia, according to the National Household Health Survey 1985 , the province of Yogyakarta had the lowest of infant mortality and was ranked high for the coverage of measles immunization and also the medical facilities in this are is relatively easy to acces. The purpose of this study was to obtain the case fatality rates and the clinical characteristics of measles cases admitted to the hospitals in the province of Yogyakarta in the period of 1984 to 1990, leading to a comparison with data from other hospitals in Indonesia. This study comprised, a retrospective study during the period of 1984 - 1987 involving 5 hospitals in Yogyakarta municipality, and a prospective study during the period of 1988 - 1990 carried out in 9 hospitals in the province of Yogyakarta. The results showed that the percentage of under-five children suffering from measles admitted to the hospitals in the period 1984 - 1987 was higher compared to under-five children hospitalized in the period of 1988 - 1990 (60% versus 36%). Therefore, it can be concluded that there was a shift in the distribution of measles cases to older children. This was probably due to the coverage of measles immunization in Yogyakarta which was higher as compared with other places. Since younger children were already protected by immunization, a relatively more older cases were found in Yogyakarta. The case fatality rate of 0.4% (2 out of 472 cases) during the period of 1984 -1987 and 0.8% (3 out of 386 cases) during the period of 1988-1990 in Yogyakarta were much lower as compared with the data reported from other hospitals in Indonesia. Several factors such as the general health condition of the province of Yogyakarta, as well as the frequency and types of complications of the diseases and the nutritional status of the measles patients may explain the different mortality of measles patients in Yogyakarta compared that in other places in Indonesia.Key words : measles - morbidity - mortality - case fatality rate - immunization